Diseño de un aerogenerador de eje horizontal para el aprovechamiento de la energía eólica en el edificio multifamiliar número uno, de la ciudadela Julio Ordoñez de la ciudad de Loja. - Montaño Tinoco, Diego Patricio (2013)
The main objective of this research was based on the design a horizontal axis wind generator for the use of Eolic energy in the multifamiliar building number one, located at Julio Ordóñez fortress, of Loja city, supplying and satisfying the energy necessities that exist in this place. All this is carried out gathering information of the wind speed of two meteorological stations as: The Meteorological Station of the INAMI "The Argelia" and the Meteorological Station in the Area of the Energy, Industries and Natural Resources Not Renewable of the National University of Loja, to couple them to the conditions of the roof of the multifamiliar building number one. In addition, it establishes electric power consumption in the department that settle down on the fourth floor of the multifamiliar building number one. From this, the research let to design the main parts of the wind generator. After the results of the design calculations have been known, among which it is the value of the needed energy in the mentioned building, the parts that form the wind generator and the efficiency of the eolic turbine, led to establish the discussion of the results, also the conclusions on the present investigative work, as well as, to give recommendations to improve the methodology in the development of the horizontal axis wind generator.